Schisantherin A alleviates non-alcoholic fatty liver disease by restoring intestinal barrier function - Yu, Shenglan; Jiang, Jiarui; Li, Qinqin; Liu, Xuan; Wang, Zhengtao; Yang, Li; Ding, Lili (Frontiers in Cellular and Infection Microbiology, 2022)
Non-alcoholic liver disease (NAFLD) is intricately linked to dysregulation of the gut-liver axis. Here, we investigated the protective effects and possible molecular mechanism of Schisantherin A (Sin A) in a high-fat diet (HFD)-induced NAFLD mouse model. Through histological, biochemical, and molecular assay, it was observed that Sin A (80 mg/kg) potently ameliorated HFD-induced hepatic steatosis and inflammation, alleviated gut inflammation, and restored intestinal barrier function. By using intestinal permeability assays in vivo and transepithelial electrical resistance measurements in vitro, we demonstrated that Sin A effectively improved gut permeability and reduced the release of lipopolysaccharide (LPS) into circulation. In line with this, we further confirmed that suppressed LPS-TLR4 signaling is the key contributor in Sin A-mediated protection against NAFLD by pharmacologically inhibiting TLR4 signaling. Finally, we found that Sin A treatment changed the composition of gut microbiota in HFD-fed mice using 16s rRNA amplicon sequencing. Gut microbiota-depleted mice, along with antibiotic treatment, displayed diminished or even abolished Sin A-mediated beneficial effects. We conclude that Sin A is an effective and safe hepatoprotective agent against HFD-induced NAFLD by partly ameliorating gut inflammation, restoring intestinal barrier function, and regulating intestinal microbiota composition.